INFLUENCE OF LEADERSHIP AND ORGANIZATION CULTURE TOWARD THE TEACHER COMPETENCE WITH MOTIVATION AS MODERATING VARIABEL (STUDY IN SULTAN AGUNG PRIVATE JUNIOR HIGH SCHOOL PEMATANGSIANTAR) - Julyanthry, Julyanthry (JURNAL KEBANGSAAN, 2017)
The objective of this research was to test the influence of leadership, organization culture, and motivation toward the teacher competence in a partial and simultaneous way. The sample of this research was all teacher in Sultan Agung Private Junior High School Pematangsiantar whose numbers were 33 Peoples. Analyzing method used was double linear regression model. Hypothesis was tested simultaneously by using F test and partially by using T test. The result of the test were performed by the SPSS obtained the multiple regression equation : Y = 2,773 + 0,155X1 + 0,810X2 . Partially variable leadership and organization culture significant influent on teacherâs competence of Sultan Agung Private Junior High School Pematangsiantar. The result of the test were performed by moderating obtained the multiple regression equation : Y = 63,419 + 0,850 ZX1 + 3,638 ZX2 + 2,252ZX3 + 0,046 AbsX1 _ X3 + 0,110 AbsX2 _ X3., The hypotesis which shows that all five variables give positive influent on teacherâs competence. The another result of this research shows that motivation is not moderating variable in the relationship between leadership and organization culture. Motivation variable is an independent variable in relation to teacherâs competence Keywords : Leadership, Organization Culture, Motivation, and Teacherâs Competence